Implementasi Modul Wi-Fi Pada Pengontrol Saklar Listrik Berbasis Mikrokontroler - Sampurna Dadi Riskiono; BP. Putra Hermana; Rinaldy Gumilang; Arianto Arianto (PTE FTK UIN Ar-Raniry, 2018)
Accidents that often occur on the road are partly due to road crossers who do not pay attention to vehicles or users of vehicles that are crossing. For that we need a tool that can give a warning to motorists facing the crossing. By using this PIR sensor, if there is a human movement that passes through the PIR sensor, the sensor will detect the human presence. The PIR sensor will be connected to the microcontroller. In this study using Arduino Uno which is a microcontroller and PIR sensor as a sensor that detects the presence of objects both human and vehicle so that it can be used as a driver warning device against road crossers. From the results of the test shows the test results, the sensor can detect the presence of human movement with the maximum distance between the PIR sensor and the object which is ± 5 meters. When it detects human presence, the LED indicator will light up, followed by a buzzer notification.